MODEL KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI GURU SMAN 1 PRAYA KABUPATEN LOMBOK TENGAH - BAIQ BUDIATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
The right principal leadership model can affect the improvement of the quality of education according to the expected goals. Therefore, a leader is very important to choose a leadership model that will be applied and then able to develop the leadership model as a strategy to achieve the school goals that have been set. This thesis is qualitative research. Data mining is done with interview, observation, and documentation techniques. The intensive research process lasted for almost six months involving the Principal, Waka kurikulum, Waka student, and teachers at 1 Praya High School. This thesis concludes that the leadership model applied by headmaster of SMAN 1 Praya is democratic leadership. There are four types of competencies that SMAN 1 Praya teachers have, namely pedagogical, professional, personality and social. In improving the pedagogical competence of teachers, the principal conducts supervision, in improving social competence, the principal establishes good relationships and communication with teachers and employees, improves professional competence, the principal supports teachers to follow government programs related to professional improvement. As for improving personality competence, the principal directs teachers to arrive early before students come, congregational zuhur prayers, commemorations of the Prophet's Maulid every year as well as other social activities. ABSTRAKModel kepemimpinan kepala sekolah yang tepat dapat mempengaruhi peningkatan kualitas pendidikan sesuai tujuan yang diharapkan. Oleh karena itu, seorang pemimpin sangat penting memilih model kepemimpinan yang akan diterapkan kemudian mampu mengembangkan model kepemimpinan tersebut sebagai suatu strategi guna mencapai tujuan sekolah yang telah ditetapkan. Tesis ini merupakan penelitian kualitatif. Penggalian data yang dilakukan dengan teknik wawancara, observasi, dan dokumentasi. Proses penelitian intensif berlangsung selama hampir enam bulan dengan melibatkan Kepala Sekolah, Waka Kurikulum, Waka kesiswaan, dan guru-guru di SMA 1 Praya. Tesis ini menyimpulkan bahwa model kepemimpinan yang diterapkan kepala SMAN 1 Praya adalah kepemimpinan demokratis. Ada empat jenis kompetensi yang dimiliki guru SMAN 1 Praya, yaitu pedagogik, profesional, kepribadian dan sosial. Dalam meningkatkan kompetensi pedagogik guru, kepala sekolah mengadakan supervisi, dalam meningkatkan kompetensi sosial, kepala sekolah menjalin hubungan dan komunikasi baik dengan guru dan pegawai, meningkatkan kompetensi profesional, kepala sekolah mendukung guru-guru mengikuti program pemerintah terkait peningkatan profesional. Sedangkan untuk meningkatkan kompetensi kepribadian, kepala sekolah mengarahkan guru datang lebih awal sebelum murid datang, sholat zuhur berjamaah, peringatan Maulid Nabi setiap tahunnya serta kegiatan sosial lainnya.